EUROPEAN UNION – RETROSPECTION AND PROSPECTS - Gazinski, Benon (European Scientific Journal, ESJ, 2014)
European Union has entered into a turning point of its history. The number of member-states has increased nearly 5-fold. Therefore, the need of new institutional and legal solution is urgent. Political context of the undergoing integration processes is different than at the beginnings: the “cold war” is the past. The threat of large military conflict is in Europe smallish. New threats and challenging are emerging, instead of: terrorism, organized crimes and natural environment protection. There are new “actors” at the global economic and political scene – with increasing importance of China, India and other “emerging markets”. A historical perspective leads to better understanding of these processes and to find better solutions. And brings to light foundations of the European unity: common civilization values and the aim of peaceful development.